2008
DOI: 10.1080/00048670802119770
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Description of Adolescents Admitted to a Public Psychiatric Inpatient Unit and their Families

Abstract: Findings indicate the multiplicity of issues facing adolescent inpatients including psychiatric symptoms, impaired personal and family functioning and family cultural and background factors. Treatment that focuses on only some of these factors may have limited effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In the same way, in adult psychiatric populations, it has been demonstrated that illness severity is not simply a matter of diagnosis, but is related to a variety of psychosocial variables [ 20 ]. Previous studies on young clinical populations have also found that beyond psychopathology itself, socio-demographic variables [ 21 ] and family characteristics [ 9 ] influence the level of treatment received by children and adolescents with emotional and behavioural problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same way, in adult psychiatric populations, it has been demonstrated that illness severity is not simply a matter of diagnosis, but is related to a variety of psychosocial variables [ 20 ]. Previous studies on young clinical populations have also found that beyond psychopathology itself, socio-demographic variables [ 21 ] and family characteristics [ 9 ] influence the level of treatment received by children and adolescents with emotional and behavioural problems.…”
Section: Discussionmentioning
confidence: 99%
“…Problem recognition by parents and service use depends on the parents’ level of education and the amount of stress they experience [ 6 , 7 ]. It has also been shown that the intensity of treatment is associated not only with the level of psychopathology, but also with the family’s profile [ 8 , 9 ]. The organization of the healthcare system, specifically the interface between primary and specialist care, has to be considered when dealing with the help-seeking process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have investigated the characteristics of youth placed in residential programs by exploring diagnoses, previous treatment experience, and family history (Connor et al, 2004;Hussey & Guo, 2002;Lyons, LibmanMintzer, Kisiel, & Shallcross, 1998;Tonge, Hughes, Pullen, Beaufoy, & Gold, 2008). Yet, none of these studies explore characteristics of youth across multiple settings, examining common trends among the population of adolescents in wilderness and residential treatment.…”
Section: Participants In Residential and Wilderness Treatmentmentioning
confidence: 98%
“…Overall, the results of studies investigating social differences in depression are hard to summarize due to methodological differences such as the measures used to assess depression as well as social position [ 7 , 9 , 11 , 14 , 15 , 17 – 20 , 26 , 27 ]. So far most studies on social position and poor mental health in adolescence have been based on psychiatric disorders overall [ 14 , 16 , 28 , 29 ], poor mental health overall [ 6 , 8 , 10 , 12 , 13 , 16 , 30 , 31 ], or self-reported depressive symptoms [ 7 , 9 , 11 , 15 – 17 , 19 , 26 , 32 ]. Only a few studies focus on diagnosed depression or mood disorders specifically [ 18 , 20 , 27 , 33 ].…”
Section: Introductionmentioning
confidence: 99%